1981
DOI: 10.1515/bchm2.1981.362.1.763
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Aminoacylation of Asparagine-Transfer RNA Early in the Developmental Cycle ofDictyostelium discoideum:Modification Pattern and Possible Significance of the Uncharged Isoacceptor tRNA3Asn

Abstract: Changes in the pattern of isoacceptors of tRNA Asn and alterations in modification of the guanine residue 34, the first position of the anticodon of tRNA Asn , have been observed in eukaryotes during differentiation. We use Dictyostelium discoideum as a model system to elucidate the possible involvement of tRNA Asn in developmental processes.Vegetative amoebae were induced to undergo developmental transition by nutrient starvation. Since amino acid starvation alone is a specific stimulus initiating development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The importance of Q, however, was clearly shown in the case of Asn Dictysteliwn discoidewn (30), where G-tRNA was specifically present during developmental transition of vegetative amobae caused by nutrient starvation. G-tRNA was completely deacylated in vivo, while Q-tRNAAs was aminoacylated (also see 25).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of Q, however, was clearly shown in the case of Asn Dictysteliwn discoidewn (30), where G-tRNA was specifically present during developmental transition of vegetative amobae caused by nutrient starvation. G-tRNA was completely deacylated in vivo, while Q-tRNAAs was aminoacylated (also see 25).…”
Section: Discussionmentioning
confidence: 98%
“…tRNAs with G in place of Q accumulate in foetal and regenerating rat liver and in a variety of animal tumours (Okada et al, Kersten, 1982). Germ-free mice, fed on a defined diet, do not synthesize queuine de novo, indicating that the modification is derived from nutrition or from the intestinal flora (Farkas, 1980; Reyniers et a!., 1981).We have shown that in Dictyostelium discoideum the extent of Q modification in the Q family of tRNAs changes during development and depends on the environmental conditions (Kersten, 1982;Dingermann et al, 1981 ; Ott et al, 1982). Non-axenic strains of the slime mould are Ahhreriurion : Q. queuosine ( 7 4 ((4.5-cis-dihydroxy-2-cyclopenten-1 -yl)-amino)-methyl)-7-deazaguanosine].…”
mentioning
confidence: 75%
“…We have shown that in Dictyostelium discoideum the extent of Q modification in the Q family of tRNAs changes during development and depends on the environmental conditions (Kersten, 1982;Dingermann et al, 1981 ; Ott et al, 1982). Non-axenic strains of the slime mould are Ahhreriurion : Q. queuosine ( 7 4 ((4.5-cis-dihydroxy-2-cyclopenten-1 -yl)-amino)-methyl)-7-deazaguanosine].…”
Section: Introductionmentioning
confidence: 97%